IMPROVING THE STUDENTS’ ACHIEVEMENT IN WRITING ANECDOTE TEXT TROUGH SPIDER MAP TECHNIQUE - Rafani Syaddanur Lubis; Sumarsih Sumarsih (Universitas Negeri Medan, 2012)
This study attempts to improve students’ achievement in writing through Spider Map Technique. The subject of this research was the class IX of SMP N 1 Ranto Baek. The number of the students in this class was 30 students and was conducted in two cycles. The instruments for collecting data were quantitative (writing test) and qualitative data (diary notes, interview). Based on the data analysis, it can be seen that there is a difference of the students’ achievement in cycle I and cycle II. In the Pre-test the mean of the students’ score was 57.2, in the Post-test I the mean of the students’ score was 69.8, and in the Post-test II the mean of the student’s score was 81.8. Based on the diary notes and interview, it showed that the expression and excitement of the students were also improved. It was found that teaching writing anecdote by using Spider Map Technique could improve. It is suggested that English teachers apply this Spider Map Technique as one of the alternatives in teaching writing anecdote. Keywords : writing, anecdote, Spider Map